DETERMINING GENDER AS PERSONAL CHARACTERISTIC THAT INFLUENCE UTILIZATION OF ONLINE LIBRARY SERVICES BY DISTANCE STUDENTS AT THE UNIVERSITY OF NAIROBI, KENYA - Gor, Peter Ochieng; Mbwesa, Prof. K. Joyce; Charles, Prof. Rambo M. (IJRDO- Journal of Educational Research, 2016)
The purpose of this study was to determine factors influencing utilization of online library services bydistance students at the University of Nairobi. Specifically the study sought to achieve one objective; toexamine how gender as a personal characteristic influence utilization of online library services bydistance students at the university of Nairobi. The researcher applied an eclecticism research paradigm.The study adopted descriptive survey design. Data was collected using self-administered questionnaireand interview schedule. The study targeted a total of 1000 students and 14 librarians in the school ofcontinuing and distance education. The sample therefore comprised of 278 distance students and 14librarians. A pilot study was conducted with 28 student respondents and 1 librarian. This constituted30% of the study sample. The reliability of the instruments was 0.72. The researcher applied captiveaudience technique to collect data from the respondents. Data were analysed using frequency counts, themean and standard deviation and hypothesis was tested using Chi-square, T-test, one way ANOVA andRegression analysis at0.05 level of significance. The key findings revealed that, there was no significantrelationship between distance students gender and utilization of online library services at the Universityof Nairobi. For example, 49.3% of the male respondents considered using online library services daily,twice and once a week compared to 13.6% of the female gender. The findings have importantimplications in utilization of online library services. For instance, all distance students irrespective oftheir gender should be encouraged to use online library services provided by the university. A study maybe carried out to investigate the effects of personal characteristics and institutional based factors oneffective utilization of online library services in private universities. The researcher considered theethical considerations so as to avoid plagiarism and ensured confidentiality.